Mandibular Canine Index as A Tool in Gender Identification - A Study in Malwa Population - Sandhya Jain1 , Merin Kuriakose2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Teeth are the hardest tissue in the body. Mandibular canines are important tooth in the human body which shows significant sexual dimorphism. Mandibular canine index can be used for gender identification during mass disasters and crime scenes. The purpose of this study was to investigate the accuracy with which gender can be differentiated in Malwa population by using the Mandibular Canine Index and sexual dimorphism. Materials and Method: The study sample includes 300 Mandibular casts of people residing in Malwa. It included 137 males and 163 female participants. Mesio distal diameter of mandibular canines were measured from mesial contact point to distal contact point of right and left mandibular canines. Inter canine distance was measured between tips of both canines. These were used for deriving MCI and determining sexual dimorphism exhibited by mandibular canines. Results: The mesiodistal width of mandibular canine were larger in males than in females. The mean difference of MCI between males and females were more on the left canine, thus making it highly significant (P Value<0.001). The standard mandibular canine index for Malwa population was obtained as 0.262. Sexual dimorphism of right mandibular canine was estimated as 4.30% and for left mandibular canine was 5.58%. Sexual dimorphism of mandibular canine is more on left side. The overall percentage accuracy of sex prediction using standard mandibular canine was found to be 65.52%. Conclusion: Tooth remains obtained from crime scenes or disasters can be used for gender identification as this method is very simple, accurate and useful.